Influence of the Projectile Rotation on the Supersonic Fluidic Element - Yufang Wang; Nannan Wang (Aerospace, 2022)
The effects of projectile rotation on the internal and external flow fields of the supersonic fluidic element are numerically studied using sliding grid technique and the RNG k-ε turbulence model. The effects of rotating speed on internal and external flow fields, switching time and output characteristics are studied. The results show that: for the external flow field, there is no obvious change in the flow field structure at low angular velocity; when the angular velocity increases to 20 r/s, the flow field structure becomes obviously asymmetric due to the Coriolis force; the flow field far away from the surface of the projectile body (more than 0.3 m) is much more affected than the flow field near the surface of the projectile body. The influence of projectile rotation on the internal flow field is much weaker than on the external flow field, and the change of internal flow field is not obvious when the rotational speed is less than 20 r/s. The switching time decreases with the increase in angular velocity, and within normal range of the angular velocity, the deviation of switching time from that without rotation is within 5%. The change of thrust distribution is not obvious when the rotational speed is less than 20 r/s. However, when the rotational speed reaches 50 r/s, the thrust of the middle part of the right nozzle increases by about 20 N.